Comparison of gestational age assessment methods in the second and third trimesters: Evaluating alternative approaches against ultrasound in urban Burkina Faso - Ouattara, Cheick Ahmed; Compaoré, Anderson; Ouédraogo, Lionel Olivier; Ouédraogo, Moctar; Ouattara, Hermann; Coulibaly, Moussa; Deng, Lishi; Nikiéma, Zakari; Hanley-Cook, Giles T.; Argaw, Alemayehu; Huybregts, Lieven; Hadush, Kokeb Tesfamariam; et al. (MDPI, 2025)
Background: Accurate determination of gestational age by way of ultrasound is challenging in resource-limited settings like Burkina Faso, leading to the use of alternative methods, though their accuracy and agreement remain poorly established. This practice leads to inadequate risk assessment during pregnancy and failure to identify preterm birth, potentially contributing to high neonatal mortality rates. The purpose of this study was to determine the agreement among alternative methods for gestational age estimation and the Alliance for Maternal and Newborn Health Improvement (AMANHI) method in Burkina Faso. Methods: Data were obtained from a prospective cohort study involving pregnant women in the second or third trimester in Bobo-Dioulasso to evaluate the agreement of last menstrual period (LMP), symphysis-fundal height (SFH), Dubowitz, Hadlock, and AMAHNI methods to estimate gestational age. The degree of agreement was assessed using the Bland–Altman method and intraclass correlation coefficients. The AMANHI method, validated for late pregnancy, was used as the reference standard. Results: A total of 768 pregnant women were included in the analysis. Plots showed a lack of agreement between the AMANHI method and all other methods, with 95% limits of agreement ranging from −7.6 to +9.8 weeks. Additionally, the incidence of preterm birth was consistently higher when assessed using the alternative methods compared with the AMANHI method. Conclusions: The clinical methods (SFH, LMP, Dubowitz) disagree with the ultrasound methods (AMANHI, Hadlock), but the ultrasound methods produce more similar results. The routine application of other methods is likely to result in an overestimation of preterm birth incidence compared with AMANHI. These findings highlight the urgent need to improve access to obstetric ultrasound and to provide comprehensive training in the application of the AMANHI method for accurate late-term gestational age estimation in Burkina Faso.